The creative training idea book : inspired tips and techniques for engaging and effective learning - Lucas, Robert W. (AMACOM, American Management Association, 2003)
Trainers have to be creative if they want their participants to feel excited, challenged, and involved. The Creative Training Idea Book is packed with instructions for using activities, games, puzzles, toys, and props to increase energy and active participation in the classroom, and reveals how to think creatively about training in any situation. Based on the author's nearly three decades of training experience, this invaluable resource gives trainers the tools to adopt a fun, energetic approach that will make for a stimulating learning environment.